The Relationship of Anxiety and Depression with the Frequency of Seizure Awakening in Epileptic Patients at Dr. Moewardi Hospital Surakarta - Trisnanti Dewi Islami; Mulia Sari; Rhomadon Apdani; Rozaq Noor Hakim; Wijaya Kusuma; Rohmaningtyas Hidayah Setyaningrum; Debree Septiawan (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: Epilepsy is the most frequent neurological disorder worldwide. Epilepsy is a disease associated with stress and anxiety, not only as a result of the disease process but also as a cause of disease recurrence. Anxiety and depression also involve stress management and often overlap with epilepsy. Determine the relationship between anxiety and depression and the frequency of seizure awakening in epilepsy patients at Dr. Moewardi Hospital, Surakarta. Methods: observational using a cross-sectional design with a quantitative approach and descriptive data processing. The purposive sampling method selected the 34 study subjects. Selected subjects meet the inclusion criteria and are willing to provide informed consent. The research was conducted at Dr. Moewardi Hospital. A normality test was performed with the Spearman correlation test. Results: The analysis of the variables indicated a significant relationship between anxiety and the frequency of seizure awakenings, as evidenced by a p-value of 0.000, which is less than 0.05. A correlation coefficient value of 0.745 indicates a strong and positive relationship category. The relationship between depression and the frequency of seizure awakening was significant because the p-value was 0.000 < 0.05. The correlation coefficient value of 0.642 indicates moderate and positive relationship categories. Conclusion: There is a significant relationship between anxiety and depression and the frequency of seizure awakening in epilepsy patients at Dr. Moewardi Hospital. Anxiety and depression increase the incidence of seizure awakening in epilepsy patients at Dr. Moewardi Hospital.